Exploration of Rural Adolescent Female's Experiences with Menstrual Health Education and Knowledge - Haley Townsend; Sara Kaylor; Delaney Johnson (Rural Nurse Organization; Binghamton University, 2023)
Purpose: The purpose of this qualitative study was to explore the experiences of rural adolescent girls surrounding menstrual health knowledge and experiences.  Sample: Twenty-five participants met selection criteria; aged 15-18, enrolled at a high school in rural Alabama and willing to share experiences.  Method: Reflective journaling guided by moderator questioning, through a one-hour educational course elicited rich descriptions of lived experiences. Data consisted of journal responses to protect the privacy of participant answers. Saldana's First Cycle/Second Cycle constant comparative method was used for data analysis.  Findings: Three themes including feelings of isolation, desire for continued and consistent education, empowerment to influence were discovered. One subtheme of increased female involvement was also discovered. Overall, participants felt alone in their quest for knowledge concerning menstrual health as they entered adolescence and desired more education as well as discussions and guidance from their female relatives. From their experiences, they wish to empower younger girls with knowledge.  Conclusions: Participants in this study experienced period poverty, defined as the lack of access to menstrual health knowledge and education, as described in current literature. Rural girls may disproportionately experience period poverty due to already present disparities. Earlier and consistently timed education should take place in the home and educational setting to empower young girls to equip them with needed knowledge and reduce stigma surrounding their menstrual cycles.  Keywords: period poverty, women's health, menstruation, reproductive health DOI:  https://doi.org/10.14574/ojrnhc.v23i1.735